10th‐grade use of cannabis: Combustible, edible, and vaporized. Issue 11 (17th October 2018) - Unknown
Abstract : Most 10th graders in this 2015 survey who ever used cannabis reported using at least two types of products among edible, vaporized, and combustible. And more than 61% of the youths — with an average age of 16 — had already used marijuana.